Empathetic examination of the contextual situations of e-government adoption initiatives by Zimbabwean citizens - Giyane, Maxmillan; Ruvinga, Caroline; Mutembedza, Amanda N.; Zhou, Tinashe G.; Punungwe, Chritopher; Mamboko, Patrick; Rebanowako, Taurai G. (A Global Society for Multidisciplinary Research, 2016)
This paper seeks to empathetically examine the contextual situations of adopting e-Government initiatives by the citizens of Zimbabwe using the Unified Theory of Acceptance and Use of Technology (UTAUT). Literature study on e-Government combined with questionnaire survey findings were used to determine the behaviours and perceptions of the citizens acting as drivers and hindrances towards the adoption of e-Government in Zimbabwe. The questionnaire survey targeted respondents seeking services from the Home Affairs Ministry in Zimbabwe’s three major cities (Harare, Bulawayo and Gweru). The study findings revealed three key drivers namely: social influences (peer influence (55%)), performance expectancy (perceived usefulness (72%)) and effort expectancy (perceived ease of use (79%)). Facilitating conditions was noted to be the key barrier manifesting itself as citizens’ lack of trust (security and privacy (53%)) in e-Government usage, the perceived high cost of doing business over the internet and lack of awareness of the e-Government initiative and its benefits. The study winds off by proffering recommendations to tackle the identified barriers in order to improve acceptance of the e-Government services by Zimbabwean citizens.